2013
DOI: 10.4300/jgme-d-12-00183.1
|View full text |Cite
|
Sign up to set email alerts
|

Current Practice in End-of-Residency Handoffs: A Survey of Internal Medicine–Pediatrics Program Directors

Abstract: Background End-of-residency outpatient handoffs affect at least 1 million patients per year, yet there is no consensus on best practices. Objective To explore the use of formal systems for end-of-residency clinic handoffs in internal medicine–pediatrics residency (Med-Peds) programs, and their associated categorical internal medicine and pediatrics programs. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…A survey 39 found that only 34% of programs had a year-end handoff process to transition patients from outgoing postgraduate year 3 (PGY-3) residents to incoming PGY-1 residents. Of the 6 articles focusing on ambulatory handoffs, only 3 implemented standardized documentation processes, [40][41][42] and no changes in patient-level outcomes were noted. Doctoroff et al 43 found that residents' patients have lessrobust outpatient follow-up after hospitalization as compared with patients with faculty primary care physicians (PCPs).…”
Section: Clinic Redesignmentioning
confidence: 99%
“…A survey 39 found that only 34% of programs had a year-end handoff process to transition patients from outgoing postgraduate year 3 (PGY-3) residents to incoming PGY-1 residents. Of the 6 articles focusing on ambulatory handoffs, only 3 implemented standardized documentation processes, [40][41][42] and no changes in patient-level outcomes were noted. Doctoroff et al 43 found that residents' patients have lessrobust outpatient follow-up after hospitalization as compared with patients with faculty primary care physicians (PCPs).…”
Section: Clinic Redesignmentioning
confidence: 99%
“…They found that fewer than half of the responder programs (31/67) had an outpatient handoff system, and the characteristics of those systems were highly variable. 10 In evaluating the scope of what should be included in a handoff, one study revealed that 87% of residents wanted written handoffs for patients with complex medical or social issues, while only 35% felt it would be useful for patients with no significant issues. 11 Handoffs with a structure similar to inpatient handoffs, including a brief summary of active medical conditions and a clinical task list, have been suggested as the most useful format.…”
Section: Introductionmentioning
confidence: 99%
“…2,5,6 Despite the risks of clinic handoffs, few residency programs have outpatient handoff systems in place, and the few interventions that address clinic handoffs have not reported sustained improvements in patient safety. [7][8][9][10][11][12][13] A multifaceted intervention in psychiatry improved timely follow-up after the clinic handoff. 8,9 In internal medicine, one standardized sign-out intervention improved the number of completed clinical tasks after a clinic handoff and another improved the number of handoffs completed by residents.…”
mentioning
confidence: 99%